Aid, Infrastructure, and FDI: Assessing the Transmission Channel with a New Index of Infrastructure - Julian Donaubauer; Birgit Meyer; Peter Nunnekamp (FIW - Research Centre International Economics, 2015)
We raise the hypothesis that aid specifically targeted at economic infrastructure helps developing countries attract higher FDI inflows through improving their endowment with infrastructure in transportation, communication, energy and finance. By performing 3SLS estimations we explicitly account for dependencies between three structural equations on the allocation of sector-specific aid, the determinants of infrastructure, and the determinants of FDI. We find fairly strong and robust evidence that targeted aid promotes FDI indirectly through the infrastructure channel. In addition, aid in infrastructure appears to have surprisingly strong direct effects on FDI.
Keywords: F21; F35; O18; 330; aid effectiveness; sector-specific aid; foreign direct investment; infrastructure